Study of the expression of cellulose synthase genes during plant growth of flax - T. A. Bazanov; I. V. Ushapovsky; N. N. Loginova; E. V. Minina; P. D. Veresova (Аграрная наука Евро-Северо-Востока, 2024)
During the selection of crops aimed at creating high-fiber varieties, it is important to determine the patterns of fiber formation at the molecular level and the genotype specificity of cellulose synthesis processes, to study the efficiency of the genes responsible for cellulose synthesis at various stages of plant ontogenesis. The aim of the work was to study the expression of flax cellulose synthase genes. The objects of the study were 8 samples of flax (genus Linum), differing in fiber content: 7 cultivarеs of Linum usitatissimum L., of which 5 cultivarеs of fiber flax, 2 cultivarеs of oilseed flax, as well as one sample of large-flowered flax (L. grandiflorum Desf.). The studied cultivar were grown in a growth chamber. Samples of plant material were taken on the 10th, 20th, 30th, 40th and 50th day after germination. RNA extraction and cDNA synthesis were carried out. RNA sequences of CesA1, CesA4, CesA6, CesA7 were obtained and gene-specific primers for PCR were developed. Gene expression was determined by semi-quantitative RT-PCR, and reaction products were separated by size using a 1.2% agarose gel. Based on the data obtained, the presence of phase- and genotype-specificity in the process of expression of cellulose synthases of the CesA family in the flax stem was established. Cellulose synthases of the primary cell wall of flax (CesA1, CesA6) show a dynamic increase in expression up to the «herringbone» stage, and then the expression gradually decreases towards the onset of rapid growth phase, while cellulose synthases of the secondary cell wall (CESA4, CESA7) are characterized by a constant increase in expression from the first days of the development of seedlings to the phase of rapid growth.